Hysterectomy A Comprehensive Surgical Approach (Springer International Publishing, 2018)
This book describes the practical performance of different hysterectomies with conventional and robotically assisted laparoscopy, laparotomy and vaginal surgery. Hysterectomy - A Practical Guide looks at the laparoscopic procedures followed by the traditional techniques of hysterectomy with laparotomy and vaginal surgery.